2021
DOI: 10.3390/ma14010192
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Coke Layers Situation in the Cohesive Zone of Blast Furnace

Abstract: Coke is the only batch component that does not soften in blast furnace thermal conditions. It is especially important at the temperatures of the cohesive zone forming because coke layers are the only gas-permeable charge. The aim of the work described in this article is the identification of individual coke layers situation in the cohesive zone. Numerical calculations of the cohesive zone situation are based on the horizontal below burden probe measures, however, coke layers are calculated using analytical geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Ramm, who first noticed the dependence of coke consumption on the share of wustite direct and indirect reduction. A support algorithm for fuel consumption optimization was successfully implemented in blast furnace practice [28,29]. The shared principles of optimal direct reduction rate (d DR ) and indirect reduction rate (d IR ) adopted to ISP technology are shown in Figure 6.…”
Section: Fuel Rate Minimization Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramm, who first noticed the dependence of coke consumption on the share of wustite direct and indirect reduction. A support algorithm for fuel consumption optimization was successfully implemented in blast furnace practice [28,29]. The shared principles of optimal direct reduction rate (d DR ) and indirect reduction rate (d IR ) adopted to ISP technology are shown in Figure 6.…”
Section: Fuel Rate Minimization Model Constructionmentioning
confidence: 99%
“…A group of modelling techniques should also be mentioned whose task is to minimize fuel consumption while maintaining the chemical efficiency of the metallurgical aggregate [26][27][28][29][30].…”
mentioning
confidence: 99%
“…One of the ways of increasing the efficiency of the blast furnace process is to optimise the charge for the production of pig iron, primarily from the viewpoint of achieving minimum coke consumption. In a series of works by leading blast furnace experts [1][2][3][4][5][6][7][8], it has been convincingly demonstrated that minimum coke consumption can be achieved with an optimal ratio of direct and indirect reduction. A realistic indicator forecast of the share of direct and indirect reduction makes it possible to increase the reporting quality of analytical diagrams and, using them, to compile a shaft that ensures the minimum level of energy demand.…”
Section: Introductionmentioning
confidence: 99%